Perceptual factors and Nigerian immigrants in Johannesburg: a study of the role of Nigerian-South African intermarriages in social integration - Oluwafemi, Adeagbo (My University, 2011)
This study seeks to understand how the general assumptions, perceptions, and representations of Nigerian immigrants shape marriages between Nigerian men and South African women in Johannesburg. It looks at the impact of prejudice on marriages between Nigerian men and South African women in an environment of generalized xenophobia and anti-Nigerian sentiments. This study looks into the private lives of intermarried couples, how they negotiate everyday discriminations and prejudices and the impact the usual general violent attacks and media reports bring upon their marriage. The major purpose of this study is to look at the impact of xenophobia and discrimination against Nigerian-South African marriages in Johannesburg. The study finds that despite the discriminations and prejudices directed against Nigerian immigrants in Johannesburg, Nigerian-South African couples often adopt love and humour to negotiate such discriminations. Also, the role of religion, particularly, the church in preaching and promoting love and unity among intermarried couples in this study is also significant. Further, this study finds that despite different contacts between Nigerian immigrants and South Africans through intermarriages, Nigerian husbands are subjected to close scrutiny to prove their innocence or confirm their guilt. Accordingly, the levels of integration differ among couples. Also, the study finds that this contact between Nigerian immigrants and South Africans is changing the perceptions and pre-conceived generalizations that all Nigerians are bad. The study is based on data gathered from a 4-month ethnographic fieldwork (August-November 2010) among Nigerian immigrants, South Africans and others (non-South Africans) in Johannesburg, South Africa. The data was collected through interviews of Nigerian immigrants, Nigerian husbands and their South African wives, friends and families. I interviewed 15 couples (Nigerian-South African couples), of both young and old marriages. The study uses Alba and Nee’s (2003) ‘intermarriage and assimilation theory’ which was originally applied in America to show the importance of intermarriage as the major indicator of integration. The context was quite different from South African context due to South Africa’s unique history and concept of marriage as well as the importance of other factors like employment, legal status etc as indicators of integration. Although this theory also works in the South African context by promoting more personal contacts between Nigerian immigrants and South Africans (particularly black South Africans), the continuous scrutiny of identity and integrity of Nigerian husbands make its operation different from where it was originally applied. Therefore, there were no absolutes in applying this theory in a South African context because intermarriage does not depict integration since other factors like employment and legal status play important roles in the integration process